2002
DOI: 10.1103/physrevlett.88.155701
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Transition of Solid Rare Gases in Confined Environments

Abstract: We report the results of x-ray diffraction and small angle scattering studies of Ar and Kr confined in sol-gel and Vycor glasses. The confined liquid crystallizes in a disordered hcp structure on freezing. Upon further cooling a sharp transition occurs at a reduced temperature of T/T(m) approximately 0.65, where the crystalline structure disappears and the total scattering decreases. This behavior marks the onset of a well-defined mobility transition, where the confined sample migrates out of the pore space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Utilizing welldefined porous systems, they found that ͑1͒ x-ray diffraction peaks of frozen Kr phase in large pores can be explained by a finite-size closest-packed crystallite model with appropriate geometry and degrees of disorder, and that ͑2͒, on the other hand, there is no evidence indicating the formation of crystalline phase in pores as small as 8 KrKr in diameter, where KrKr is the diameter of a Kr atom, which is 3.65 Å. These results are in qualitative agreement with reports for other confined rare-gas systems such as Kr or Xe in silica gel, 1 Ar or Kr in Vycor glass, 2,4,5 Ar in Gelsil, 2 …”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Utilizing welldefined porous systems, they found that ͑1͒ x-ray diffraction peaks of frozen Kr phase in large pores can be explained by a finite-size closest-packed crystallite model with appropriate geometry and degrees of disorder, and that ͑2͒, on the other hand, there is no evidence indicating the formation of crystalline phase in pores as small as 8 KrKr in diameter, where KrKr is the diameter of a Kr atom, which is 3.65 Å. These results are in qualitative agreement with reports for other confined rare-gas systems such as Kr or Xe in silica gel, 1 Ar or Kr in Vycor glass, 2,4,5 Ar in Gelsil, 2 …”
Section: Introductionsupporting
confidence: 87%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] The scope of interest ranges from nonpolar, polar, organic to metallic systems. Above all, rare-gas systems, such as argon ͑Ar͒, krypton ͑Kr͒, and xenon ͑Xe͒, are expected to provide a basic knowledge of the freezing phenomena of confined materials because these systems consist of simple spherical atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The results provide a basis for the interpretation of experiments on freezing in such materials, particularly 1 H-NMR and scattering experiments. DOI Freezing and melting in nanoporous materials is of fundamental interest in understanding the effect of confinement, reduced dimension, and surface forces on the thermodynamics of fluids [1][2][3][4][5]. Shifts in the freezing temperature and, in some cases, new surface-or confinement-induced phases, are observed on reducing the width of the confined space to approach the range of the intermolecular forces [6,7].…”
mentioning
confidence: 99%
“…in a wider sense than a restriction by walls. Free clusters formed in expanded gas jet [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], deposits on substrate at relatively high supersaturations [1,2,4], impurity-helium solids created by injection of particles into superfluid 4 He [23][24][25] as well as adsorbates grown inside of nanoporous materials [26][27][28][29][30][31][32][33][34] are typical examples of such a confinement. Remarkable similarity, that was found earlier [32] between electron diffraction data obtained in gas adiabatic experiments and from clusters formed in nanoporous confinement of amorphous carbon, was ascribed to the growth 'inward' processes, which are characteristic for crystallization in both cases.…”
Section: Introductionmentioning
confidence: 99%